(untitled) (Research, Society and Development, 2020)
The objective was to analyze the formative proposal of the National Camp of Development and Technical Improvement of the Confederação Brasileira de Handebol. While studying ex-post facto, documents and images of the Campsites were consulted. The activities indicate a formative triad, articulated between training session, video analysis and competition, with rules and norms of behavior related to the content of the training sessions. The sessions guided the implantation of a standard systematized by the technical coordinator of the Confederation. It is concluded that the process of sports development, through the Camp, enables a learning environment immersed in positive values of the sport practice for young handball athletes.